Functional Anatomy of the kidney of the Buffaloes - Alaa A.Sawad (Basrah Journal of Veterinary Research)
The morphology and the Vasculaturc of the ltdncy of the Buffaloes was escr: lei lined BL.lfI‘t-11005 kidneys was eorrc at u. Information obtained from gross dissection o em )1 . Th‘ f wtionrll with latex and Cold cure solution injected vascular and in excI‘et0TY 035” " u‘ ‘ signiﬁcance of the renal apparatus was discussed